Secondary aorto-enteric fistula presenting over a 2-month period with recurrent gastrointestinal bleeding. (15th April 2013) - Jamal, K; Shaunak, S; Kalsi, S; Nehra, D
Abstract : A female in her sixties presented with recurrent gastrointestinal bleeding over a two-month period requiring multiple hospital admissions. Inconclusive upper and lower gastrointestinal endoscopies in addition to an initial negative CT angiogram initially left the diagnosis uncertain. A subsequent catastrophic bleed prompted a further CT angiogram that demonstrated a fistula between the aorta and third part of the duodenum with active contrast extravasation. Emergency surgery was carried out but ultimately the patient did not survive.